3, 6‐Dimethoxy‐6″, 6″‐Dimethyl‐(7, 8, 2″, 3″)‐Chromeneflavone, a Flavonoid Isolated from Lonchocarpus Araripensis Benth. (Fabaceae), Reduces Nociceptive Behaviour in Mice. (14th July 2015) - Almeida, Jackson R. G. S.; Silva, Juliane C.; Guimarães, Amanda L.; Oliveira, Ana P.; Souza, Grasielly R.; Oliveira‐Júnior, Raimundo G.; Lima‐Saraiva, Sarah R. G.; Barbosa‐Filho, José M.; Braz‐Filho, Raimundo; Queiroz, Dinalva Brito; Botelho, Marco Antônio
<x xml:space="preserve">Abstract</x> Lonchocarpus araripensis Benth. is largely distributed in the northeast region of Brazil. It is popularly known as 'sucupira'. Recent studies have shown that some species of Lonchocarpus have interesting pharmacological activities. In this study, we evaluated the antinociceptive effect of a flavone isolated from L. araripensis. The chemical examination resulted in the isolation of 3, 6‐dimethoxy‐6″, 6″‐dimethyl‐(7, 8, 2″, 3″)‐chromeneflavone (DDF). The structure of the compound was established by spectral analysis. Antinociceptive activity of DDF was evaluated by measuring nociception by acetic acid, formalin and hot plate tests. The rota rod test was used to evaluate motor coordination. The results demonstrated that DDF was able to prevent acetic‐acid‐writhing‐induced nociception (p < 0.001) in mice. Furthermore, DDF produced a significant reduction of the nociceptive behaviour at the early and late phases of paw licking in the formalin test. Also, DDF produced an inhibition of the nociceptive behaviour during a hot‐plate test. No alteration in motor coordination was observed. These results confirm the hypothesis that DDF reduces the nociceptive behaviour in mice, probably through central mechanisms, but without compromising the motor coordination of animals. Copyright © 2015 John Wiley & Sons, Ltd.